A formação continuada de professores, profissionais da educação e colaboradores na perspectiva da inclusão escolar - Buss, Joziane Jaske (2021)
The purpose of this research is to analyze, in the continuous formation of teachers (regent teachers, teachers from specific areas, Specialized Educational Assistance teachers), education professionals (school supervisors, area coordinators, principals), and collaborators (Special Education assistants, kindergarten assistants, librarians, school secretaries, trainees, janitors, cooks, drivers), at the municipality of Santa Maria de Jetibá, ES, Brazil, both challenges and inclusion possibilities for students with deficiency. Continuous formation’s challenges under the school-inclusion perspective are here discussed, based on contextual demands, to build other, possible dialogues, actions and practices making access, permanence, apprenticeship and development of students with deficiency possible, considering the importance of the construction of a collective knowledge-production space. To develop this discussion, we present, for the theoretical dialogue, the contributions by Lev Semyonovich Vygotsky, António Nóvoa, and authors that have been debating the teachers’ continuous formation to aim at inclusion in school. Methodology has designed a qualitative research, with a case study of the ethnographic type, research subjects being the teachers, education professionals and education collaborators. As a data-generation instrument, participantobservation, open and closed formularies, semi-structured interviewes and focus groups havebeen used. Data have demonstrated the importance of the constitution of formative spaces committed with the creation of a team, marked by the exchange of several knowledge kinds, by the collaboration and participation of all members in school inclusion. We consider that it is in the group that possibilities are built, for continuous formation to become a transformation tool in the pedagogical practices, thus tightening the bonds between all education professionalsand the scientific-pedagogical knowledge kinds. As an end-product of this dissertation, we have prepared some short-play videos about school inclusion and the importance of the constitution of collective formative spaces in the school’s ambit, considering the challenges found in the schooling of students with deficiency, published on the Youtube channel of the Municipality of Santa Maria de Jetibá and on the website of the Secretariat of Education of that municipality.